2022
DOI: 10.1039/d2mh00644h
|View full text |Cite
|
Sign up to set email alerts
|

Control of up-to-down/down-to-up light-induced ferroelectric polarization reversal

Abstract: Light control of ferroelectric polarization is of interest for exploitation of ferroelectric thin films in ultrafast data storage and logic functionalities. The rapidly oscillating electric field of light absorbed in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(70 reference statements)
0
5
1
Order By: Relevance
“…In a summary of Figure 1, our real-time investigations allow us to conclude that exposure to above-bandgap UV light gives rise to a transient enhancement or suppression of the polarization in single-domain PZT 20/80 films that depends in magnitude on the pristine direction of the out-of-plane polarization. Interestingly, these findings seem to indicate a different microscopic origin of the light-induced response compared to previous reports on BaTiO 3 and PZT films [18,20,30,17], where UV-light exposure has been shown to restore the the as-grown polarization orientation, independent of the initial out-of-plane direction.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…In a summary of Figure 1, our real-time investigations allow us to conclude that exposure to above-bandgap UV light gives rise to a transient enhancement or suppression of the polarization in single-domain PZT 20/80 films that depends in magnitude on the pristine direction of the out-of-plane polarization. Interestingly, these findings seem to indicate a different microscopic origin of the light-induced response compared to previous reports on BaTiO 3 and PZT films [18,20,30,17], where UV-light exposure has been shown to restore the the as-grown polarization orientation, independent of the initial out-of-plane direction.…”
Section: Resultscontrasting
confidence: 79%
“…Furthermore, in ferroelectric thin films and heterostructures the presence of surfaces and interfaces can cause strong perturbation of the electronic band structure and, thus introduce extrinsic effects that dominate over the photoresponse of the ferroelectric bulk. In this context, several recent studies on the optical erasure of written domains [17,18,19,20] and the optical manipulation of domain walls [21,22] have highlighted the influence of interfaces on the optical response in ferroelectric thin films. Despite these efforts, the interplay between the photoresponse of the ferroelectric bulk and the role of interfaces is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Fina et al , the choice of the bottom electrode in a BaTiO 3 films allowed the creation of imprint fields ( E imp ) that point either upwards or downwards or have negligible effects. 44 These imprint fields played a crucial role in determining the polar state of the as-grown BaTiO 3 film, which ultimately governed the photo-induced polarization switching. As shown in Fig.…”
Section: Non-chemical Modulation Engineering Of Ferroelectrics and Mu...mentioning
confidence: 99%
“…The regulating strategy employing force/pressure/stress and negative pressure involves the use of common external stimuli to control ferroelectrics and multiferroics, which act by modifying factors such as lattice structure, symmetry, ion displacement, electromagnetic interactions and electronic structure, thereby inuencing the ferroelectric and ferromagnetic properties of multiferroic materials. [42][43][44] On a microscopic level, the change in the interatomic or intermolecular distances in a material can result in enhanced interaction forces between atoms or molecules and give rise to new phenomena that are not observed under normal pressure conditions. Previous studies have shown that by subjecting the traditional proton-ordered ferroelectric material KH 2 PO 4 (KDP) to pressure testing, the material undergoes a phase transition from its original ferroelectric phase to a paraelectric phase when the applied pressure reaches a certain value.…”
Section: Introductionmentioning
confidence: 99%
“…Among those methods, optical modulation is one of the most convenient and flexible ways to interact with the polarization order. Their interaction can be classified as a thermoelectric effect induced by high-intensity laser illumination, , bulk photovoltaic effect owing to the noncentrosymmetric crystal structure, , and interfacial photovoltaic effect induced by interface doping. , Optical-induced polarization switching based on the thermoelectric effect is always irreversible and destructive. A former research achieved reversible control of ferroelectric polarization based on the bulk photovoltaic effect, while that occurs only with certain crystal orientation or light polarization.…”
Section: Introductionmentioning
confidence: 99%